Adaptive anatomical structure for nastic movement in Mimosa pudica L. - Chen, Ming-Lin; Mao, Wen-Bin; Cui, Mei-Chen (Bangladesh Journal of Botany, 2013)
In order to study the adaptive anatomical structures during nastic movement of Mimosa pudica L., anatomical structures of main pulvinus, common petioles, rachis and leaflets were compared with Albizia julibrissin Durazz. (taken as control). The anatomical structures of main pulvinus and common petiole of M. pudica were different from that of A. julibrissin. Upon stimuliti, the protoplast volume of M. pudica in the lower cortical parenchyma cells become smaller than that in upper ones, a feature seldom found in A. julibrissin. There were found many reticulate lacunas on the two side of adaxial petiole of M. pudica, but nil in A. julibrissin. Similarly some ill developed lacunas were found in the pulvinus of rachis and leaflet of M. pudica, but absent in A. julibrissin. It appears that reticulate lacunas in common petiole of M. pudica are responsible for its strong nastic movement. The main sensitivity position lies at the base of common petiole, where the lower cortex is more sensitive than the upper cortex, and the ordinal sensitivity positions are rachis and leaflets. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15876 Bangladesh J. Bot. 42(1): 131-137, 2013 (June)